العقيدة الأمنية الجزائرية وإشكالية التكيف مع التهديدات الجديدة - بوسكين, سليم (جامعة الوادي University of Eloued, 2019)
الملخص: تتغير العقائد الأمنية للدول بتغير صناع القرار والأيديولوجية والنسق العقدي (خاصة في حالة قيام ثورات أو تغير جذري في النسق السياسي)، أو بتغير طبيعة ونمط التهديدات والتحديات الأمنية التي تواجه الدولة. وقد شهدت البيئة الأمنية للجزائر في السنوات الأخيرة تحولا وتغيرا في طبيعة ونمط التهديدات والتحديات خاصة بعد أزمات دول الجوار (مالي وليبيا) والاضطرابات السياسية والأمنية في المنطقة المغاربية والساحلية، هذا ما فرض على صناع القرار مرونة في التعاطي مع المبادئ المُؤَسِسَة للعقيدة الأمنية وإجراء بعض التعديلات الجزئية عليها بما يمثل تكيّفا مع المستجدات الأمنية في المحيط الإقليمي من أجل حماية الأمن والمصالح الوطنية. Abstract: The security doctrines of countries change with the change of decision-makers, ideology, and belief system (especially in the case of revolutions and radical change), or change in the nature and pattern of threats and security challenges facing the state. In recent years, Algeria's security environment has undergone a change in the nature and pattern of threats and challenges, especially after the crises of the neighboring countries (Mali and Libya) and the political and security unrest in the Maghreb and Sahal areas. This has forced the decision makers to be flexible in dealing with the founding principles of the Algerian security doctrine In accordance with security developments in the regional environment in order to protect national security and interests.
Keywords: الأمن ; العقيدة الأمنية ; الجزائر ; التهديدات الأمنية الجديدة ; التحديات الأمنية; Security ; Security doctrine; Algeria ; New security threats; Security challenges